Islam Nusantara and the Legitimacy of the Qur’an: A Reading of the Principle of Al-‘Urf in Ibn ‘Āshūr’s Tafsir and Abdurrahman Wahid’s Indigenization of Islam - Jamila, Winni Sabron; Rifdi, Moh.; Maulana, M. Rizki (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Islam Nusantara is a discourse that has generated diverse responses, ranging from support to rejection. One of the prominent figures who strongly supports this discourse is Abdurrahman Wahid (Gus Dur). Through library-based research, this article examines the concept of Islam Nusantara from Gus Dur’s perspective. The findings indicate that Gus Dur’s support for Islam Nusantara is grounded in two primary considerations. First, Islam Nusantara is viewed as an effort to balance the process of Arabization, which has the potential to cultivate fanaticism toward Arabic symbols and diminish local cultural identities. Second, Islam Nusantara is understood as a form of dialogue between religious texts and the socio-cultural realities of the Nusantara region, resulting in a distinctive mode of Islamic practice without compromising the essential teachings of Islam.